Preserving the Environment within the ASEAN Skies: Lessons from the European Union Emissions Trading Scheme - Nugraha, Ridha Aditya (Hasanuddin University, 2018)
The United Nations Framework Convention on Climate Change also known as the Kyoto Protocol has set up a framework to reduce carbon emission. The environmental issue is also being addressed at the international aviation sector through the International Civil Aviation Organizationâs resolutions. As an international organization sui generis, the European Union (EU) has decided to take up a further step with the enactment of the EU Emissions Trading Scheme. The latter has obliged both EU and non-EU airlines to comply with its ambitious goal controlling aviation emissions. However, the legal framework had triggered international objections from legal perspective due to infringement towards the Chicago Convention of 1944 and the international customary law principles. Considering of the nature of the Association of South East Asian Nations (ASEAN) as an international organization without a supranational law order; as well as recent developments in regards to legal framework on emissions, the future of ASEAN skies from an environmental perspective seems uncertain. However, if ASEAN Emissions Trading Scheme shall take place, they should learn from the EU Emissions Trading Scheme past mistakes and the International Civil Aviation Organization resolutions to prevent non-discrimination towards non-ASEAN member statesâ airlines from happening.